The effect of gluteus medius training on hip kinematics in a runner with iliotibial band syndrome - R. Schreiber; Q. Louw (AOSIS, 2011)
Iliotibial  band  syndrome  (ITBS)  is  a  common  clinical  presentation in  runners.  There  are  several  hypotheses  to  explain  this  condition  including  faulty  control of the hip joint in the frontal plane during the stance phase of running. It is postulated that improving activity in the gluteus medius muscle may assist in produc-ing  more  appropriate  stabilization and  therefore  reduce  the  stress  on  the  Iliotibial band  (ITB).  This  single  case  study  provides  an  interesting  clinical  scenario  where a single-subject with ITBS was measured for hip kinematics during running, before and after a trial period of classic gluteus medius exercises. The biomechanical data show an initial (pre-intervention) increase in adduction position during the stance phase of running on the affected side (in contrast to the unaffected side). This was measured using a Moven motion analysis suit. After the trial intervention period, the relative position of the affected hip had reduced in adduction at both heel strike and at 30° knee flexion. This study provides support  for the theory that hip control in the frontal plane may be a contributing factor in ITBS. Clinicians are encouraged to monitor hip control as well as ITBS symptoms when they utilise this gluteus medius protocol. Further research to establish whether change in pelvic control results in decrease in ITBS symptoms is warranted.